What is the consciousness, literacy and behaviour of Italian Gen-Z towards the protection of the marine environment? - FORLEO, MARIA BONAVENTURA; BREDICE, MARILENA (Mediterranean Marine Science, 2024)
The study explores Italian Generation Z’s consciousness, literacy and behaviour towards marine environmental issues aimed at detecting whether different profiles of people exist. A survey was implemented with 778 students attending upper secondary schools. Descriptive statistics, significance tests for differences among groups, and cluster analysis were applied. Gen Z expresses concern and awareness about environmental issues, but not high levels of engagement in marine pro-environmental behaviours. Only about half of the sample solved six of the twelve objective knowledge questions correctly, and some misconceptions were observed. Gender, education, and area of living differentiate answers over several phenomena. Cluster results highlight four groups of young people with different sustainability profiles, two of which showed sensitiveness and awareness about the investigated topics, while the other groups are insensitive, unaware, and illiterate. The poor knowledge of Italian Generation Z about ocean sustainability topics highlighted the need to further educate young people to become literate individuals.